Automated beta zone parapapillary area measurement to differentiate between healthy and glaucoma eyes - Manalastas, Patricia Isabel C.; Belghith, Akram; Weinreb, Robert N.; Jonas, Jost B.; Suh, Min Hee; Yarmohammadi, Adeleh; Medeiros, Felipe A.; Girkin, Christopher A.; Liebmann, Jeffrey M.; Zangwill, Linda M. (American journal of ophthalmology, 2018)
Purpose - To evaluate whether automated assessment of beta zone parapapillary atrophy (βPPA) area can differentiate between glaucomatous and healthy eyes of varying axial lengths (AL). - Design - Cross-sectional study. - Methods - βPPA was automatically identified in glaucoma and healthy eyes with enhanced-depth imaging optical coherence tomography (OCT) optic nerve head (ONH) radial B-scans. Associations with AL and the presence of glaucoma were assessed. Manually delineated βPPA on individual OCT ONH B-scans of 35 eyes from the Diagnostic Innovations in Glaucoma Study served to validate the automated method. - Results - One hundred fifty-three glaucoma eyes (mean ± standard deviation) (visual field mean deviation, -5.0 ± 6.4 dB and mean AL, 25.1 ± 1.1 mm) and 73 healthy eyes (visual field mean deviation, 0.1 ± 1.4 dB and mean AL, 24.1 ± 1.1 mm) were included. In multivariable analysis, larger βPPA area was significantly associated with a diagnosis of glaucoma after controlling for age, central corneal thickness, and AL. Moreover, in multivariable analysis, the odds of having glaucoma were doubled for each 0.2 mm2 larger βPPA area. The age- and AL-adjusted area under the receiver operating characteristic curve (95% confidence interval) of βPPA area for differentiating between glaucoma and healthy eyes was 0.75 (0.68-0.81). Agreement for the location of the Bruch membrane opening and the location of retinal pigment epithelium tips was stronger between the automated technique and each individual observer than it was between the 2 observers. - Conclusions - Larger βPPA area, as determined by automated OCT assessment, is significantly associated with a diagnosis of glaucoma, even after adjusting for age and AL, and may aid in differentiating healthy from glaucomatous eyes.
Available online 9 May 2018
Gesehen am 10.10.2019